‘Interactions with purpose’: Exploring staff understandings of student engagement in a university with an ethos of staff-student partnership - Flint, Abbi; Millard, Luke (International Journal for Students as Partners, 2018)
This paper describes qualitative research that used concept-map mediated interviews to explore academic staff understandings of student engagement, within a UK university with an explicit ethos of student engagement through partnership. The research explored how staff conceptualised student engagement and how it was experienced through practice. Our findings indicate that understandings of student engagement are highly individual and contextual and were framed in diverse ways by our participants. However, there were features that cut across these diverse understandings. Reflecting on the difference between staff-student partnership and other forms of engagement, we suggest partnership can be distinguished by an understanding of engagement as a relationship between staff and students, and through the way features and values are put into practice.